Finnish Retirement and Aging Study: a prospective cohort study - Stenholm Sari; Suorsa Kristin; Leskinen Tuija; Myllyntausta Saana; Pulakka Anna; Pentti Jaana; Vahtera Jussi (British Medical Journal Publishing Group, 2025)
Purpose The Finnish Retirement and Aging (FIREA) Study was set up to study changes in health behavioural and cardiometabolic risk factors across retirement transition, and to examine the long-term consequences of work and retirement on health and functioning with advancing age.Participants Public sector workers whose estimated statutory retirement date was in 2014{\textendash}2019 were invited to participate by sending them a questionnaire 18 months prior to their estimated retirement date. In the first phase of the FIREA Study, participants were followed up with annual surveys, accelerometer and clinical measurements during retirement transition into post-retirement years. The FIREA survey cohort includes 6783 participants, of which 908 belong also to the activity substudy and 290 to the clinical substudy.Findings to date Collected data include survey measures about health, lifestyle factors, psychosocial distress, work-related factors as well as retirement intentions. Accelerometer and GPS devices are used to measure 24-hour movement behaviours. Clinical examination includes blood and hair sample, measurements of anthropometry, cardiovascular function, physical fitness, physical and cognitive function. Our results suggest that in general retirement transition seems to have beneficial influence on health behaviours as well as on physical and mental health, but there are large individual differences, and certain behaviours such as sedentariness tend to increase especially among those retiring from manual occupations.Future plans The second phase of the FIREA Study will be conducted during 2023{\textendash}2025, when participants are 70 years old. The FIREA Study welcomes research collaboration proposals that fall within the general aims of the project.Data are available upon reasonable request. Anonymised partial datasets of the FIREA study may be shared on a case-by-case basis upon request for bona fide researchers with an established scientific record and bona fide organisations. Data sharing outside the group is done in collaboration with FIREA group and requires a data-sharing agreement. Investigators can submit an expression of interest to FIREA research group at University of Turku, Finland (firea@utu.fi).